Mathematical model for considering the change in heater capacity for proportional temperature regulator of the hybrid-film microthermostat; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 4 : Power engineering - Karaban V. M. (Power engineering, 2007)
Заглавие с титульного листа